FEMINISME DALAM BINGKAI FIKIH KLASIK SUARA YANG DIBUNGKAM - Alwathani, Muharrir (Yayasan An-Nur Meunara Baro, 2025)
This article explores the intersection of feminism and classical Islamic jurisprudence by uncovering the silenced voices of women hidden within patriarchal-dominated scholarly traditions. Employing a deconstructive, genealogical, and feminist ethnographic approach, the study reveals the existence of fiqh manuscripts authored or interpolated by female scholars, often disguised through metaphors, poetry, and narratives. These findings challenge the notion that women lacked contribution in classical fiqh by demonstrating that their marginalization was a result of structural suppression rather than absence. The discussion delves into the anatomy of silencing within Islamic knowledge traditions, subversive strategies employed by women, and the potential for reinterpreting fiqh through a gendered lens in the contemporary context. The study further underscores the need to reconstruct traditional fiqh curricula based on gender justice, paving the way for a more inclusive Islamic discourse. This article makes a significant contribution to the revival of female narratives in classical Islamic scholarship and supports the advancement of contextual and progressive Islamic feminist thought.